2011
DOI: 10.1016/j.devcel.2011.03.019
|View full text |Cite
|
Sign up to set email alerts
|

LEAFY Target Genes Reveal Floral Regulatory Logic, cis Motifs, and a Link to Biotic Stimulus Response

Abstract: The transition from vegetative growth to flower formation is critical for the survival of flowering plants. The plant-specific transcription factor LEAFY (LFY) has central, evolutionarily conserved roles in this process, both in the formation of the first flower and later in floral patterning. We performed genome-wide binding and expression studies to elucidate the molecular mechanisms by which LFY executes these roles. Our study reveals that LFY directs an elaborate regulatory network in control of floral hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
305
2
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(331 citation statements)
references
References 89 publications
(140 reference statements)
15
305
2
9
Order By: Relevance
“…Recently, regulatory networks underlying important developmental processes such as flowering time and floral patterning have been elucidated in Arabidopsis (Kaufmann et al 2009(Kaufmann et al , 2010Pastore et al 2011;Winter et al 2011). Although these programs are largely conserved across eudicots, we know little about how such mechanisms extend to grasses and/or to what extent novel factors have been recruited to pattern grass-specific inflorescence morphology.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, regulatory networks underlying important developmental processes such as flowering time and floral patterning have been elucidated in Arabidopsis (Kaufmann et al 2009(Kaufmann et al , 2010Pastore et al 2011;Winter et al 2011). Although these programs are largely conserved across eudicots, we know little about how such mechanisms extend to grasses and/or to what extent novel factors have been recruited to pattern grass-specific inflorescence morphology.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…3J; Supplemental Table S11; Kaufmann et al 2009). Recent work from Arabidopsis showed that bZIPs and MADS-box TFs are likely co-factors of LFY in promoting floral differentiation (Winter et al 2011;Wu et al 2012) and thus may play qualitatively similar roles in maize in promoting branch determinacy.…”
Section: Co-expression Signatures Across Spatiotemporal and Genetic Cmentioning
confidence: 99%
“…LFY is considered to be one of the key floral meristem iden- tity genes, and regulates many other downstream floral meristem identity genes (Weigel et al, 1992;Winter et al, 2011). In addition to its role in determining floral meristem identity, LFY has also been shown to regulate flowering time in Arabidopsis (Blazquez et …”
Section: The Function Of Lfy Is Not Limited To Determining Floral Orgmentioning
confidence: 99%
“…The expression of genes functioning in meristem identity transition was mis-regulated in the pkl-1 mutant, including LFY and many other floral homeotic genes. LFY is considered to be a key regulator of meristem identity transition, and also functions to activate the expression of its downstream floral homeotic genes via its binding to the specific regulatory elements close to transcription starting sites of its downstream genes, thereby to direct floral organ patterning (Weigel et al, 1992;Weigel and Nilsson, 1995;Winter et al, 2011). Our RNA-seq data showed that LFY and 14 LFY-regulated downstream genes were differentially regulated in the pkl-1 mutant ( Figure 5A, Table S3 in Supporting Information), and these genes can be mainly sorted into flowering time and floral homeotic groups (Winter et al, 2011).…”
Section: Expression Of a Set Of Flowering-related Genes Is Affected Bmentioning
confidence: 99%
See 1 more Smart Citation